Can Private Sector fill the gap in Agricultural Extension? - Babu, Suresh Chandra (2015)
By: Suresh Babu The structural adjustments of the 1980s and 1990s led to drastic fiscal cuts in financing of public extension systems causing their near collapse in many developing countries. Several new players tried to enter and fill the vacuum, including the private sector. Yet it is not clear how much and how well the private sector is able to fill the gap left by the dysfunctional public systems. This seminar is based on a recent book titled Knowledge Driven Development: Global Lessons from Private Extension (2015, Elsevier), a collection of case studies evaluating 10 private extension models in seven developing countries. The book assesses the functioning of private sector extension systems in various contextual settings. Common knowledge is that most private sector extension models are implemented for, and seem to work well for farmers selling high value commodities. But for staple commodity growers (such as cereal growers), with a small market surplus and little scope for contract farming, these systems may not be sustainable due to cost factors. Some of the case studies challenges this conventional wisdom. Lessons drawn from the cases could be important in giving direction to future development, research and policy on private extension systems. It is observed that private companies have created shared value for farmers across all cases. Integrated services provided as part of private extension programs were a major contributing factor for their success. Private extension programs also help in the effective use of technology for increasing farmer productivity. Additionally, they provide assured market access and price to contracted farmers, thereby reducing the uncertainty of demand to a great extent. Extension programs implemented by private companies lead to inclusive innovation by engaging farmers in development of technical and market solutions. They also reduce barriers to accessing quality inputs. Further, they tend to induce collective action amongst farmer groups, increasing solidarity. Private extension is demand driven, directly addresses information needs of contract farmers, and under certain conditions can fill the gap left by public extension systems in developing countries.